EKSPOR KOMODITI DASAR PADAT KARYA INDONESIA, 2000-2009 - Abuzar Asra (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2011)
during 2000-2009, Indonesia’s export of labor intensive primary commodities grew faster than the growth of Indonesia’s total export, indicating its increasing role in Indonesia’s trade. Most of this export went to three countries: Japan, America and Singapore (JAS). The available information shows that the share of Indonesia’s labor intensive primary commodities in the JAS’ import of these commodities increased during 2000-2009, while the share of Indonesia’s export to JAS’ total import remained the same. It shows that the level of market penetration of labor intensive primary commodities to JAS was higher than that of all commodities. This study uses the constant market share (cms) Analysis to evaluate the performance of Indonesia’s export of labor intensive primary commodities to JAS during the 2000’s. CMS analysis finds that during the 2000’s, with the exception of 2000-2003, Indonesia’s total export and export of labor intensive primary commodities to JAS rose in line with the increase in world’s export to these three countries. on the whole, except for 2006-2009, the export performance of Indonesia’s labor intensive primary commodities to JAS was better than the performance of Indonesia’s total export to JAS. This is due to the positive effect of both commodity composition and competitiveness during 2000-2003 and 2003-2006. For 2006-2009, the performance of Indonesia’s export of labor intensive primary commodities to JAS, relative to the world’s export of the same commodities to JAS, was discouraging, due to a significantly negative commodity composition effect. As export of these commodities, especially to JAS, is important, viewed from both employment creation and foreign exchange generation, it is then necessary to find ways to improve its performance.